Effect of salsolinol on ACTH and cortisol response to handling stress in early anestrous sheep - Małgorzata Hasiec; Michał Szlis; Natalia Chmielewska; Konrad Górski; Katarzyna Romanowicz; Tomasz Misztal (Czech Journal of Animal Science, 2017)
Inhibition of hypothalamic-pituitary-adrenal (HPA) axis activity by salsolinol was demonstrated in lactating sheep. We assessed whether salsolinol regulates, besides lactation, also adrenocorticotropic hormone (ACTH) and cortisol release, and if its action is prolactin-dependent. We examined two groups of early anestrous sheep, which received for three days salsolinol or vehicle-only intracerebroventricular injections, and a group of lactating sheep injected with the vehicle only. On day 3, blood samples were collected for over six hours and the anterior pituitary was dissected. Plasma ACTH, cortisol, and prolactin concentrations, and proopiomelanocortin (POMC) and prolactin (PRL) mRNA expression within the anterior pituitary were assayed. In all groups, ACTH and cortisol concentrations were higher (P < 0.05 and P < 0.001) during the first half of sampling than in the second half; there were no differences in prolactin concentration. Lactating sheep had lower (P < 0.05 and P < 0.001) plasma ACTH and cortisol concentrations and higher (P < 0.001) plasma prolactin concentration than both groups of anestrous sheep during the first half of sampling. In the second half, there were no differences in ACTH and cortisol concentrations between all groups, but prolactin concentration was still higher (P < 0.001) in lactating animals. Salsolinol treatment decreased ACTH and cortisol concentrations during the first half of sampling (P < 0.05 and P < 0.001) compared to the anestrous controls, but had no effect on prolactin concentration. POMC mRNA expression was lower (P < 0.05) and PRL mRNA expression was higher (P < 0.05) in lactating sheep than in anestrous sheep. Salsolinol did not affect POMC and PRL mRNA expression. In conclusion, increased ACTH and cortisol concentrations during the first half of sampling occurred in response to handling stress. Salsolinol inhibited the HPA axis response to stress in early anestrous sheep, and it was unrelated to prolactin secretion.